2021
DOI: 10.1097/aco.0000000000001008
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative laboratory testing in elderly patients

Abstract: Purpose of review Preoperative testing in elderly patients is performed to examine the patient's current medical condition in the context of evaluating vulnerabilities and predicting postoperative complications to ensure that all functions recover before surgery. This review focused on preoperative laboratory tests in geriatric patients. Recent findings Preoperative complete blood count, electrolyte testing, and blood chemistry can predict postoperative complications. Preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Similarly, almost 27.72% of hospital patients may experience hypocalcemia, and the incidence was the highest in patients over 65 years [ 31 ]. Regarding the harm of hypocalcemia, a recent review summarized the relationships between preoperative hypocalcemia and postoperative adverse complications in elderly patients [ 32 ], and another systematic review found admission hypocalcemia was associated with increased mortality in trauma patients [ 18 ]. These findings suggest that clinicians should pay attention to hypocalcemia because of life-threatening consequence [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, almost 27.72% of hospital patients may experience hypocalcemia, and the incidence was the highest in patients over 65 years [ 31 ]. Regarding the harm of hypocalcemia, a recent review summarized the relationships between preoperative hypocalcemia and postoperative adverse complications in elderly patients [ 32 ], and another systematic review found admission hypocalcemia was associated with increased mortality in trauma patients [ 18 ]. These findings suggest that clinicians should pay attention to hypocalcemia because of life-threatening consequence [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vakumlu jelli tüplere alınan kan örnekleri (1500 g' de (28). Geriatrik hastalarla yürütülmüş olan bir çalışmada preoperatif hipoalbumineminin operasyon sonrası 1 yıllık izlemde artmış mortalite oranı ile birlikte olduğu gösterilmiştir (29) Acil serviste geriatrik hastalarla yürütülmüş olan bir başka çalışmada da nötrofil/lenfosit oranı ve CRP/albumin oranının bu hasta grubu için mortalite belirleyicisi olabileceği öne sürülmüştür (30) Biz de çalışmamızda hem ABH olan olgularda hem de erken kaybedilen olgularımızda belirgin albümin düşüklüğünün olduğunu gözlemledik. Çalışma sonuçlarına dayanarak yaşlı yoğun bakım hastaları için serum albümin seviyesinin erken dönem mortalitesini ön görmede etkin, kolay ve ulaşılabilir bir parametre olabileceğini söyleyebiliriz.…”
Section: Laboratuvar Parametreleriunclassified